PENGARUH PEMAHAMAN TASAWUF DAN INTEGRASI ILMU PENGETAHUAN TERHADAP KEHIDUPAN SOSIAL MAHASISWA UNIVERSITAS SUNAN GIRI SURABAYA - Idris, Mochammad; Solchan Ghozali (As-Sulthan Journal of Education, 2025)
This study examines the influence of Sufism understanding and knowledge integration on students' social lives. Using a quantitative approach, data were collected through a Likert-scale questionnaire measuring Sufism understanding, knowledge integration, and students' social lives at Sunan Giri University, Surabaya. Multiple linear regression was used as the analysis technique, and validity and reliability tests ensured data quality. The results indicate that Sufism understanding and knowledge integration significantly influence students' social lives. The integration of Sufism teachings into students' academic and social lives can strengthen their social character and interpersonal relationships. This study recommends that universities integrate spiritual values ​​into their educational curricula. However, this study's limitation is the limited sample size; therefore, further research with a larger sample size is recommended for more representative results.